Analisis Manajemen Pengendalian Waktu dengan Pendekatan Metode CPM & PERT pada Proyek Peningkatan Jalan Alternatif Medan - Brastagi - Kutalimbaru - Siregar, Arya Ahrilsyah; Lubis, Kamaluddin (Portal: Jurnal Teknik Sipil, 2025)
Road infrastructure is a crucial factor in supporting the economic growth of a region. Therefore, the provision of appropriate road infrastructure through adequate investment budget allocation is essential for regional economic development. Investments in road and bridge construction have a broad impact, benefiting both users and the overall development of the area. This study employs the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT), with a case study on the Medan–Brastagi–Kutalimbaru road. The primary objective is to determine the critical path and calculate the cost implications of project acceleration using the PERT crashing method on this alternative route.The implementation of the PERT method identifies the critical path involving activities A, D, E, and F, with an estimated project completion time of 129.6 days (rounded to 130 days) and a success probability of 99.99%. Using the CPM method, the project can be expedited by 15 days with an additional cost of Rp 22,560,000.00, whereas the PERT method allows for a 13-day reduction with an additional cost of Rp 16,920,000.00. The standard project duration is set at 130 days, with the CPM method optimizing it to 128 days, while the PERT method shortens the initial project duration from 143 days to 130 days.These findings indicate that the application of the crash program method for project acceleration affects scheduling and leads to changes in project implementation costs.